Battle for the Bildungsroman: 'protagonicity' and national allegory. Issue 12 (1st December 2020) - Ormsbee, Michael
ABSTRACT: The scope of the Bildungsroman is infamously variable. Given a wide enough definition, the genre can conceivably become coterminous with the novel itself; given a narrow enough definition it threatens to disappear entirely. This variability is not the insurmountable obstacle that some critics have supposed. By taking seriously both a wide and a narrow definition of the Bildungsroman, I argue that there exists a common denominator linking the widest and narrowest senses of the genre; namely, the orientation towards the 'single individual'. Through a reading of Jane Eyre, I argue further that the question of how to recognise a Bildungsroman when we read one turns out to depend a great deal on the question of how we identify a character as a protagonist in the first place. The 'battle for the Bildungsroman' refers to a figurative struggle-unto-death between characters that takes place in the minds of readers, the purpose of which is to clinch a character's right to be perceived as protagonist. At that point, however, protagonists are often claimed as allegorical vehicles for certain nations, making the Bildungsroman itself seem always on the verge of disappearing into national allegory.